ENHANCING TEACHER SELF-EFFICACY: A FRAMEWORK FOR STRUCTURED CONTINUOUS PROFESSIONAL DEVELOPMENT - Novariza, Bobi (Managere: Indonesian Journal of Educational Management, 2023)
This research aims to analyze the influence of the sustainability of the professionalism management development (PKB) program on teacher self-efficacy in Islamic Islamic madrasahs. This research is motivated by the importance of increasing teacher competence and self-confidence in teaching through a structured and systematic CPD program. This research uses a qualitative descriptive method, with data obtained through interviews, observation and documentation, which is then analyzed using triangulation techniques. The research results show that good CPD management which includes planning, implementation, monitoring and reporting has a positive effect on teacher self-efficacy. Teachers with high self-efficacy are more confident in managing the classroom and implementing innovative teaching methods. Findings also show that professional collaboration, such as in Teacher Working Groups (KKG), and participation in professional networks, such as teacher communities and educational organizations, make significant contributions in increasing teacher self-efficacy. Therefore, effective management of PKB as well as support for collaboration and professional networks are very important to improve the quality of education in madrasah ibtidaiyah.